THE EFFECT OF WORKING CONDITIONS ON EMPLOYEE RETENTION AMONG GEN Z EMPLOYEES IN THE MANUFACTURING INDUSTRY PT WIDIA SAMI NIKI - Febriyana, Faradila; Dwianto, Agung Surya (Jurnal Education and Development, 2026)
Indonesia, as a developing country, still relies on the manufacturing industry as a source of national employment. The workforce has characteristics that meet companies' needs, but as time goes by, Generation Z has emerged as a problem for companies that are less effective at retaining their employees. Generation Z, with its unique characteristics, poses a challenge to employee retention for companies. This study uses quantitative methods and questionnaire data. The research was conducted at PT Widia Sami Niki with a sample of 30 respondents. The results indicate that working conditions have a significant positive relationship with employee retention. Working conditions have the greatest contribution to employees' decisions to stay, compared to compensation and career development factors. The greater the organization's efforts to provide comfort for employees, the more likely they are to stay with the organization.